Uma análise da estratégia de adaptação de produto considerando a influência de valores religiosos no consumo: o caso da Sadia - Ferreira, Gleriani Torres Carbone (2010)
Although most of the GDP and employment in most countries continue to depend more activities geared towards the domestic economy than activities focused on the global market, in fact what happens to competition in those foreign markets that determines the percentage wealth appropriated by business and, ultimately, by the people of each country (Castells, 1999). In this context, the export is of great importance for the company because it is the most effective way to secure their own future in a globalized environment increasingly competitive, requiring full capacity of Brazilian companies to undercut foreign competition, both in Brazil abroad. For Brazil, the export activity is also strategically important as it contributes to income generation and employment, for the entry of foreign currency needed to balance the external accounts and the promotion of economic development. Thus, our object of study is the production and export of chicken meat, making a strategic look on the shares of Sadia, a Brazilian company that was consolidated in the adaptation of fresh chicken meat, and several other products to cater to consumers Muslim adherents to Islam, where we observe the requirements according to the principles of the Quran, known as Halal Slaughter